Brachiaria grass inoculated with Azospirillum brasilense submitted to nitrogen fertilization (Research, Society and Development, 2022)
The objective was to evaluate the effect of Azospirillum brasilense associated with nitrogen fertilization on the production and quality of Brachiaria decumbens. The experiment was carried out in a 2x4 factorial arrangement, with four replications. The treatments consisted of two factors: with and without inoculation with A. brasilense and four doses of N (0, 40, 80, 120 kg/ha). The characteristics evaluated were: leaf area index (LAI), light interception (LI), tillers population density (TPD), SPAD index, leaf/stem ratio, natural matter production (NM), dry matter production (DM) and chemical-bromatological analyses. Higher LI and LAI results were observed, respectively, with 62.2 and 74.4 kg/ha N. The inoculation provided higher TPD up to 80 kg/ha N; increases of 11, 15 and 18.2% of SPAD index, respectively at doses of 40, 80 and 120 kg/ha of N and increased in the production of NM and DM. There was a linear increase in crude protein levels with N doses. Inoculation increased total carbohydrate levels with 40 and 80 kg/ha of N. Azospirillum brasilense contributes positively to the development, production and quality of Brachiaria decumbens when associated with a dose of up to 80 kg/ha nitrogen.